Anopheles gambiae sensu stricto Aquatic Stages Development Comparison between Insectary and Semifield Structure. (5th January 2015) - Kweka, Eliningaya J.; Tenu, Filemoni; Magogo, Frank; Mboera, Leonard E. G.
Abstract : Effective malaria vector control initiatives need a clear understanding of mosquito behaviour and its ecology. This study compared larvae development to adult emergence in insectary and malaria-sphere (SFS). This is the preliminary study which gives an insight to forthcoming studies. Anopheles gambiae sensu stricto eggs were hatched in insectary and transferred in densities of 20 and 50 per microhabitat with twenty replicates of each density. Both densities of larvae were reared in semifield structure and in insectary from the same batch of eggs. They were provided with tetramin fish food. In both densities of 20 and 50, pupation rate and time were found to be similar in SFS and insectary, but, in survivorship from larvae to pupae at density of 50, more larvae survived significantly to pupae stage in SFS than in insectary (P = 0.002 ). The adult emergence rates were similar for densities of 20 and 50 between SFS and Insectary. There was a significant difference between SFS and insectary in light intensity (P = 0.001 ) and temperatures (P = 0.001 ), with SFS having higher rates than insectary. The findings of this study have shown that larvae development rates are encouraging having semifield structures for malaria vector rearing for behavioural studies toward malaria control.